PROFIL PENYIMPANAN OBAT DI INSTALASI FARMASI RSUD ANDI DJEMMA MASAMBA, KABUPATEN LUWU UTARA - achyar, lukman; Aztriana, Aztriana; Ririn, Ririn (Makassar Pharmaceutical Science Journal (MPSJ), 2023)
Pharmaceutical services, such as management including drug storage, must be considered because the treatment of various types of drugs or preparations is not the same. Drug storage is highly essential stage to maintain the quality of medicines, that drug storage must ensure the quality and safety of drugs in accordance with pharmaceutical requirements. The purpose of this study was to determine the profile of drug storage at Pharmaceutical Installation of Andi Djemma Masamba Hospital, North Luwu Regency and its compliance with applicable regulations in Indonesia. This research conducted qualitative and quantitative methods. The informants in this study consisted of the Head of Pharmaceutical Installation, Accompanying Pharmacist, and Head of Pharmacy Installation Warehouse of Andi Djemma Masamba Hospital, North Luwu Regency. The data were collected from observation, in-depth interviews, and data analysis. Presentation of conformity regarding facilities and infrastructure was found 100%. Next, the presentation of the storage place of narcotics, psychotropic substances and precursors was classified 100%. However, the presentation of drug storage methods was 88.8% which confirmed drugs were not arranged based on therapy class. The percentage of high alert drug storage methods of 80% was identified not to use the tall man lettering method. at last, presentation of 100% stock card recording has been performed on every drug mutation process.